Diplomatic criticism: a panoramic study of scientific production - Moutinho, Sonia Oliveira Matos [UNESP]; Rodriguez, Sonia Maria TROITInO [UNESP] (Univ Zaragoza, 2023)
Diplomatic Criticism is addressed based on scientific production published in international scientific databases. For this study, we used the method of applied bibliometry to identify the undisclosed scientific production on the investigated object. The investigation is exploratory-descriptive and qualitative-quantitative. As research sources, documents retrieved from Google Scholar, Web of Science and Scopus by means of the Publish or Perish software were used, in order to verify the theoretical production of the Diplomatic Criticism and the metrics of interest. RawsGraph, an open source framework used for visualizing complex data, is applied for visualizing metrics. With it, it was possible to confirm that studies on Diplomatic Criticism, in an international context, were experiencing exponential growth and had their first publication records in the year 1681.
Keywords: Diplomatic criticism; Scientific production; Bibliometric studies